2016
DOI: 10.1371/journal.pone.0160808
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Micro-RNA Expression in Pre-Eclampsia Identifies a Number of Common Pathways Associated with the Disease

Abstract: BackgroundPre-eclampsia (PE) is a complex, multi-systemic condition of pregnancy which greatly impacts maternal and perinatal morbidity and mortality. MicroRNAs (miRs) are differentially expressed in PE and may be important in helping to understand the condition and its pathogenesis.MethodsCase-control studies investigating expression of miRs in PE were collected through a systematic literature search. Data was extracted and compared from 58 studies to identify the most promising miRs associated with PE pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 177 publications
(246 reference statements)
0
51
0
1
Order By: Relevance
“…Expression analysis in placentae from PE women has shown reduced expression of members of the BMP signaling pathway (ALK1, ID1, and EGFL7) [95,104,118]. Together with the known sFLT1 and sENG biomarkers of PE, the molecular mechanism is narrowed down to the BMP signaling pathway and possible cross-talk with VEGF and NOTCH signaling.…”
Section: Preeclampsiamentioning
confidence: 99%
“…Expression analysis in placentae from PE women has shown reduced expression of members of the BMP signaling pathway (ALK1, ID1, and EGFL7) [95,104,118]. Together with the known sFLT1 and sENG biomarkers of PE, the molecular mechanism is narrowed down to the BMP signaling pathway and possible cross-talk with VEGF and NOTCH signaling.…”
Section: Preeclampsiamentioning
confidence: 99%
“…MikroRNA'lar (miRNA), 19-25 nükleotid uzunluğunda, kodlamayan, hedefleri olan mRNA'lara bağlanarak yıkımında rol oynayan ve tranlasyonu baskılayarak gen ifadesinin düzenlenmesinde görev alan küçük fonksiyonel RNA molekülleridir (1,2). Günümüzde, maternal kandaki miRNA düzeyleri ile gebeliğe özgü preeklampsi, gestasyonel diyabet (GDM) gibi çeşitli patolojiler arasındaki ilişkileri araştıran çok sayıda çalışma mevcuttur (3)(4)(5)(6)(7)(8). Maternal dolaşıma sinsityotrofoblastlardan ekzozomlar yoluyla plasental kökenli miRNA'ların salındığı belirlenmiş ve bunların tanıda önem taşıdığına dikkat çekilmiştir (7,8).…”
Section: Introductionunclassified
“…Previous studies have demonstrated that PE is a common and severe health problem for fetuses and expectant women, a leading cause of maternal and fetal mortality and morbidity (5). PE is associated with fetus maldevelopment and may lead to eclampsia and even miscarriage (5)(6)(7). Worldwide, there are ~55,000 deaths associated with PE reported annually (7), and the underlying cause of PE remains unknown.…”
Section: Introductionmentioning
confidence: 99%